2015
DOI: 10.2478/jee-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of N-Type Zinc Oxide/P-Type Boron Doped Diamond Heterojunction

Abstract: Diamond and ZnO are very promising wide-bandgap materials for electronic, photovoltaic and sensor applications because of their excellent electrical, optical, physical and electrochemical properties and biocompatibility. In this contribution we show that the combination of these two materials opens up the potential for fabrication of bipolar heterojunctions. Semiconducting boron doped diamond (BDD) thin films were grown on Si and UV grade silica glass substrates by HFCVD method with various boron concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The dependence of SiV photoluminescence activity on the deposition parameters has been systematically investigated [13][14][15][16]. It has been found that the substrate material quality has no effect on SiV [4] and PL is sensitive to the gas composition [14] and substrate temperature [15]. Optimal gas composition and substrate temperature resulting in maximal PL activity were reported in [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of SiV photoluminescence activity on the deposition parameters has been systematically investigated [13][14][15][16]. It has been found that the substrate material quality has no effect on SiV [4] and PL is sensitive to the gas composition [14] and substrate temperature [15]. Optimal gas composition and substrate temperature resulting in maximal PL activity were reported in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Diamond shows a unique combination of physical and chemical properties such as high hardness, thermal conductivity, chemical stability, wide band gap (∼ 5.5 eV) [1,2] and biocompatibility, which make it advantageous for optoelectronics [3,4] and biotechnology [5]. These applications are determined not only by the intrinsic properties of diamond but also by crystallographic defects and impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic as well as boron-doped diamonds (BBDs) have many remarkable properties for application in microelectrochemical systems such as tribotester [1], various types of resonators [2][3][4][5][6], cantilevers [7], tip probes [8] and a variety of other micro-electro-mechanical systems (MEMS) [9]. The highest hardness, tensile strength, electrical properties [10,11], possibility of long-term surface termination [12,13], large electrochemical window, low background current, mechanical and chemical stability and corrosion resistance designates diamonds a unique material in microfluidics [14][15][16].…”
Section: Introductionmentioning
confidence: 99%